2021
DOI: 10.3389/fonc.2021.746577
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Prognostic Significance of NOTCH1 Mutations in Diffuse Large B-Cell Lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous group of large lymphoid B cell malignancy with distinct clinical and genetic features. Recently, NOTCH1 mutations were identified in DLBCL cases by Next-generation sequencing (NGS), but the clinical features and prognostic impact were not systematically studied. Here, NOTCH1 genes in 161 DLBCL samples were sequenced by NGS. The prognostic value of NOTCH1 mutations was assessed in the context of clinical and laboratory factors, such as international progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…JAK-STAT signaling pathways were associated with pathogenesis of ABC-DLBCL [ 22 ]. DLBCL patients with the NOTCH1 mutations have worse PFS and OS [ 23 ]. These results are consistent with previous studies showing that the CXCR4/CXCL12 axis can mediate tumorigenicity by activating various intracellular signaling transduction pathways and downstream effectors [ 24 – 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…JAK-STAT signaling pathways were associated with pathogenesis of ABC-DLBCL [ 22 ]. DLBCL patients with the NOTCH1 mutations have worse PFS and OS [ 23 ]. These results are consistent with previous studies showing that the CXCR4/CXCL12 axis can mediate tumorigenicity by activating various intracellular signaling transduction pathways and downstream effectors [ 24 – 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 29 Recent research has indicated that mutations in NOTCH1 are present in approximately 10% of DLBCL cases. 27 It has also been suggested that Notch1 might function as a driver in the pathogenesis of certain DLBCL cases. 28 To date, there are no published studies that have examined immunostaining of the NICD domain of Notch1 specifically in DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 3 Mammals have four NOTCH receptors (NOTCH1, NOTCH2, NOTCH3, NOTCH4) with slightly different structures/functions and distinct subcellular localizations. 1 While all NOTCH receptors play some role in cancer development, this is most clear for NOTCH1, which is frequently mutated or overexpressed in breast cancer 4 , lung cancer 5 , aggressive desmoid tumors 6 and in hematological cancers, such as T-cell acute lymphoblastic leukemia (T-ALL) 7 , chronic lymphocytic leukemia (CLL) 8 , diffuse large B-cell lymphoma (DLBCL) 9 and mantle cell lymphoma (MCL) 10 . The majority of T-ALL cases harbor activating NOTCH1 mutations and therefore NOTCH1 has been actively investigated as a major target for therapy in this rare leukemia.…”
Section: Introductionmentioning
confidence: 99%